Dynamic contribution of microbial residues to soil organic matter accumulation influenced by maize straw mulching - Liu, Xiao; Zhou, Feng; Hu, Guoqing; Shao, Shuai; He, Hongbo; Zhang, Wei; Zhang, Xudong; Li, Lijun (Geoderma, 2019)
Soil degradation is a serious problem in northeast China due to the routine removal of aboveground crop residues under conventional tillage systems; thus, crop residue retention becomes an essential approach for maintaining and improving soil organic matter (SOM) in this area. However, the impact of returning crop residue on microbial-driven SOM accumulation remains unclear. In this context, an 8-year field experiment with maize straw mulching (SM) was conducted in northeast China to evaluate how maize straw return may influence the dynamic contribution of microbial residues to SOM accumulation. Conventional cultivation was used as a control (CR), in which only 10 cm of aboveground maize biomass remained after the annual harvest. Soil samples (0–10 cm) were collected after the annual harvest for the measurement of soil organic carbon (SOC) and amino sugars (AS). Based on a first-order model, we found that soil microbial residue accumulation in this temperate arable soil might reach a steady state within decades under a specific agricultural management practice. Maize straw mulching both strengthened the retention ability of soil microbial residues and expanded their accumulation capacity. According to the glucosamine to muramic acid ratio, maize straw mulching facilitated the accumulation of fungal residues more than bacterial ones. Compared to maize residue removal, maize straw mulching accelerated the accumulation of microbial residues in SOM and enhanced the contribution of microbial residues to SOM sequestration in the surface soil, likely elucidating the pivotal mechanisms by which the “4/1000” initiative goal for agricultural soil will be met, at least for the first 10 years. Because bacterial residues are actively involved in SOM turnover while fungal residues dominantly contribute to SOM accrual enhanced by maize straw return compared to maize residue removal, we conclude that SOM in this arable field might be stabilized at a higher sequestration capacity under management with maize straw mulching. •Total amino sugars increased nonlinearly with time under two field managements.•Maize straw boosted the accrual capacity of microbial residues with higher stability.•Maize straw facilitated fungal residue accumulation more than bacterial residues.•Maize straw enhanced the contribution of microbial residues to SOM sequestration.•Fungal residues favored SOM accrual, but bacterial residues increased SOM turnover.